2014
DOI: 10.1371/journal.pone.0105320
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Family Planning, Contraceptive Failure, and Unintended Pregnancy among HIV-Infected and HIV-Uninfected Women in Zimbabwe

Abstract: BackgroundPrevention of unintended pregnancies among women living with HIV infection is a strategy recommended by the World Health Organization for prevention of mother-to-child transmission of HIV (PMTCT). We assessed pregnancy intentions and contraceptive use among HIV-positive and HIV-negative women with a recent pregnancy in Zimbabwe.MethodsWe analyzed baseline data from the evaluation of Zimbabwe’s Accelerated National PMTCT Program. Eligible women were randomly sampled from the catchment areas of 157 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
65
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 26 publications
18
65
2
3
Order By: Relevance
“…However, when compared to studies from the HIV positive women, our results are consistent with unmet need among married women in Zimbabwe (16%) [17],higher than reports from prior demographic and health surveys in Kenya [18] but lower than findings from Uganda [19]. We also found higher rates of modern family planning (combination methods used 32%), compared to a previous report from Lesotho, which documented 6% in a similar population [20].…”
Section: Discussionsupporting
confidence: 86%
“…However, when compared to studies from the HIV positive women, our results are consistent with unmet need among married women in Zimbabwe (16%) [17],higher than reports from prior demographic and health surveys in Kenya [18] but lower than findings from Uganda [19]. We also found higher rates of modern family planning (combination methods used 32%), compared to a previous report from Lesotho, which documented 6% in a similar population [20].…”
Section: Discussionsupporting
confidence: 86%
“…In fact, in some countries contraceptive prevalence has recently stagnated and even declined, and unmet need for family planning in the region remains highest in the world (Cleland, Harbison, & Shah, 2014), with less than half of sub-Saharan women who said that they would like to stop or postpone childbearing using contraception (Sedgh, Hussain, Bankole, & Singh, 2007). As a result, unintended pregnancies are common (McCoy et al, 2014; Singh, Sedgh, & Hussain, 2010), compromising the health and well-being of women, children, and families.…”
Section: Background and Conceptualizationmentioning
confidence: 99%
“…Unintended pregnancy was common in our population, in which half of HIV-infected participants reported that their last pregnancy was unintended. Unintended pregnancy was also higher among HIV-infected women in Zimbabwe (McCoy et al, 2014), while most recent pregnancy intentions of postpartum women in South Africa and Swaziland did not differ by HIV status (Warren, Abuya, Askew, & Integra, 2013). Most of our HIV-infected women also did not want to have more children.…”
Section: Discussionmentioning
confidence: 98%